2015 American College of Rheumatology Guideline for the Treatment of Rheumatoid Arthritis. Issue 1 (6th November 2015) - Singh, Jasvinder A.; Saag, Kenneth G.; Bridges, S. Louis; Akl, Elie A.; Bannuru, Raveendhara R.; Sullivan, Matthew C.; Vaysbrot, Elizaveta; McNaughton, Christine; Osani, Mikala; Shmerling, Robert H.; Curtis, Jeffrey R.; Furst, Daniel E.; et al.
Abstract : Objective: To develop a new evidence‐based, pharmacologic treatment guideline for rheumatoid arthritis (RA). Methods: We conducted systematic reviews to synthesize the evidence for the benefits and harms of various treatment options. We used the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology to rate the quality of evidence. We employed a group consensus process to grade the strength of recommendations (either strong or conditional). A strong recommendation indicates that clinicians are certain that the benefits of an intervention far outweigh the harms (or vice versa). A conditional recommendation denotes uncertainty over the balance of benefits and harms and/or more significant variability in patient values and preferences. Results: The guideline covers the use of traditional disease‐modifying antirheumatic drugs (DMARDs), biologic agents, tofacitinib, and glucocorticoids in early (<6 months) and established (≥6 months) RA. In addition, it provides recommendations on using a treat‐to‐target approach, tapering and discontinuing medications, and the use of biologic agents and DMARDs in patients with hepatitis, congestive heart failure, malignancy, and serious infections. The guideline addresses the use of vaccines in patients starting/receiving DMARDs or biologic agents, screening for tuberculosis in patients starting/receiving biologic agents or tofacitinib, and laboratory monitoring for traditional DMARDs. The guideline includes 74 recommendations: 23% are strong and 77% are conditional. Conclusion: This RA guideline should serve as a tool for clinicians and patients (our two target audiences) for pharmacologic treatment decisions in commonly encountered clinical situations. These recommendations are not prescriptive, and the treatment decisions should be made by physicians and patients through a shared decision‐making process taking into account patients' values, preferences, and comorbidities. These recommendations should not be used to limit or deny access to therapies.